Sustainability of business performance: a case of Teliti Computers Sdn Bhd / Zulkifli Che Long, Norlaila Ibrahim and Zuraida Mohamad - Che Long, Zulkifli; Ibrahim, Norlaila; Mohamad, Zuraida (2010)
This study intends to look into the sustainability of business performance in ICT based company, namely Teliti Computers Sdn Bhd. As the company is located in Kerteh Terengganu, the scope of the study will focus on ICT industry in Terengganu region. The aim of this research is to analyze the current management practices by evaluating internal and external business operation of Teliti Computers - East Coast branch in Kerteh. The study come up with matching analysis, develop recommendations based on the findings of the study and finally to propose appropriate strategies to the branch operation for their sustainable business performance. The research is conducted using qualitative method in gathering primary and secondary data. By applying strategic management approach, the researcher use common business analysis techniques and performance measurement analysis to meet both objectives of the studies. The study found that, there are two types of strategies that meet with the current business operations which is market development and market penetration towards to improve the business operation and sustain the business in the long term. The three recommendations generated from the study are to conduct market research to get new market, to improve in competencies by strengthening human capital, technical skills and knowledge towards providing first level support and finally to have promotion strategy by conducting aggressive promotional activities.